Enhancement of metabolite production from HAB21 F23 an endophyte / Munirah Mohamad - Mohamad, Munirah (2008)
An endophyte HAB2 I F23 used in this study was grown in various culture conditions and the extracts were tested for antimicrobial and cytotoxic activity. The parameters that were used in this study include different form (solid, liquid) of potato dextrose media at different incubation period (one, two and four weeks), water source (tap water, deionized water) of solid and liquid potato dextrose media and 1/5 diluted solid and liquid potato dextrose media. Extracts of HAB21 F23 grown in various culture conditions exhibited considerable differences in cytotoxic activity when tested in vitro against colon cancer (HT29) cell lines and normal embryonic liver (WRL68) cell lines using the MTT assays. The results from the present study showed that among the solid media, PDA2 was the most potent with an IC50 value of 3.57 µg/ml and among the liquid media, l/5PDB was the most potent towards HT29 cell lines with an IC50 value of 0.43 µg/ml. However, the HAB2 I F23 extract was potent also against the cell lines WRL68, showing that it was not selective against cancer and normal cell lines. The HAB21 F23 extracts were also tested for antimicrobial activity against pathogenic fungi (Candida albicans, Aspergillus niger), and bacteria (Staphylococcus aureus, Bacillus subtilis, E. coli, Micrococcus luteus) using disc diffusion method but results from this study revealed that the endophyte HAB21 F23 showed no antimicrobial activity.